Economic Growth in Kosovo as a Challenge to Environmental Preservation in the Republic of Kosovo (European Journal of Marketing and Economics, 2018)
The developing economies pose a significant threat to the environment, which has become a worldwide phenomenon. The need for production, export, and economic growth poses a challenge for every government and company. The Republic of Kosovo has witnessed a considerable economic development during the recent years, but is has fallen short of considering and implementing a strategy for the preservation of the environment. Taking in account the planning and the development strategies in the Republic of Kosovo, from the side of the government and the interest of businesses to run after profit, it leads to a strong debate over the issue that is related to the process and the policies that have their implications in the preservation of the environment. The developing countries argue that they have much to do about employment, exports and an overall development of their countries. Consequently, they breach the rules and norms of environmental preservation. Kosovo is relatively rich with underground and surface resources, where there are large quantities of minerals and coal. Exploiting these resources can have a great impact on economic development. In this paper we look at the largest companies that exploit the raw materials needed for business in Kosovo, which at the same time are also the largest polluters, namely the thermo power plant Kosova B, the iron ore Ferronickel, and cement producing plant Sharrcem, the data for which were collected on site by the authors.
Keywords: Republic of Kosovo, economic growth, development, pollution.